Jurisprudence of State Administrative Courts in The Development of State Administrative Law - Aju Putrijanti (Jurnal Penelitian Hukum De Jure, 2021)
State Administrative Courts is a judicial body that has absolute competence to examine and resolve disputes in the field of state administration. The development of State Administrative Courts (Peratun) jurisprudence is indispensable for the development of state administrative law. The problems studied are the role of jurisprudence in the field of state administrative law and the role of State Administrative Courts in providing access to justice. This research is a normative legal research where primary and secondary legal materials are analyzed qualitatively. The Supreme Court has made efforts to strengthen jurisprudence so that it can support thedevelopment of administrative law. Judges’ decisions are needed as a source of law. This is because it comes from dynamic legal dispute resolution. Then, jurisprudence can bring about social change for society. The process of making judges’ decisions is also faster than the process of drafting laws. The broader absolute competence of State Administrative Courts can provide easy access to justice where the public can file complaints against factual actions of the Government in the field of public law. Jurisprudence as a source of law is indispensable for developing state administrative law by taking into account the development of society, social conditions, legal and political conditions. Jurisprudence produces general principles of good governance so that it can be used for the administration of government wisely.